Dermoscopic Characteristics of Nail Involvement in Patients with Psoriasis Vulgaris: A Descriptive Cross-Sectional Study at a Tertiary Hospital in Surakarta, Indonesia - Aulia Yasmin; Nurrachmat Mulianto; Nila Kusumasari; Laura Noviani; Dimas Arief Destiyono (Open Access Indonesian Journal of Medical Reviews, 2026)
Psoriasis vulgaris is a chronic immune-mediated inflammatory disease that frequently involves the nails, yet nail changes are often overlooked despite their diagnostic and prognostic importance. Dermoscopy (onychoscopy) is a non-invasive tool that may improve detection of nail involvement, but data from Indonesian populations are scarce. This study aimed to describe the dermoscopic characteristics of nail changes in patients with psoriasis vulgaris. A descriptive cross-sectional study was conducted on 30 adults with clinically diagnosed psoriasis vulgaris (ICD-10 L40.0) attending the Dermatology and Venereology Polyclinic of Dr. Moewardi General Hospital, Surakarta, between November and December 2024, selected by purposive sampling. Each patient underwent full clinical and dermoscopic (DermLite) nail examination with digital photography. Proportions were summarised with 95% Wilson confidence intervals (CI). Subjects were predominantly male (17; 56.7%), and the largest age group was 45–64 years (13; 43.3%). Nail changes were detected dermoscopically in 24 patients (80.0%; 95% CI 62.7–90.5). Among affected patients (n=24), the most frequent features were nail pitting (75.0%), onycholysis (62.5%), crumbling (54.2%), splinter haemorrhage (50.0%) and subungual hyperkeratosis (41.7%); less frequent were leukonychia (33.3%), Beau's lines (16.7%), oil-spot/salmon patch (12.5%) and red lunula (4.2%). Nail involvement exceeded a pooled literature reference (p=0.006); matrix and nail-bed features occurred in comparable proportions (p=0.744); and feature frequencies departed from a uniform distribution (chi-square=28.7, p<0.001). In conclusion, dermoscopic nail changes were common in psoriasis vulgaris, most often nail pitting and onycholysis. Dermoscopy is an efficient, non-invasive method that can support the diagnosis of nail psoriasis in Indonesian clinical practice.